Fresh Water : Women Writing on the Great Lakes - Swan, Alison (Book collections on Project MUSE., 2006)
Fresh Water: Women Writing on the Great Lakes is a collection of nonfiction works by women writers. These works focus on the Midwest: living with the five interconnected freshwater seas that we know as the Great Lakes. Contributing to this collection are renowned poets, essayists, and fiction writers, all of whom write about their own creative streams of consciousness, the fresh waters of the Great Lakes, and the region''s many rivers: Loraine Anderson, Judith Arcana, Rachel Azima, Mary Blocksma, Gayle Boss, Sharon Dilworth, Beth Ann Fennelly, Linda Nemec Foster, Gail Griffin, Rasma Haidri, A.